| library; |
| import self as self; |
| import "dart:core" as core; |
| |
| typedef Foo01<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = (Null) →* void; |
| typedef Foo02<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = ((Null) →* void) →* void; |
| typedef Foo03<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = (((Null) →* void) →* void) →* void; |
| typedef Foo04<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = ((((Null) →* void) →* void) →* void) →* void; |
| typedef Foo05<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = (((((Null) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo06<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = ((((((Null) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo07<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = (((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo08<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = ((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo09<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = (((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo10<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = ((((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo11<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = (((((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo12<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = ((((((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo13<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = (((((((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo14<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = ((((((((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo15<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = (((((((((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo16<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = ((((((((((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo17<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = (((((((((((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo18<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = ((((((((((((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo19<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = (((((((((((((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| typedef Foo20<unrelated X extends core::Object* = dynamic, unrelated Y extends core::Object* = dynamic, unrelated Z extends core::Object* = dynamic> = ((((((((((((((((((((Null) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void) →* void; |
| static method main() → dynamic {} |